KARAKTERISTIK PADA BALITA DIARE DENGAN INFEKSI ENTEROPATHOGENIC Escherichia coli (EPEC) DI PUSKESMAS RAWAT INAP KOTA PEKANBARU - Sabella Gustika Vernanda; Maya Savira; Dewi Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDiarrheal diseases remain one of the leading cause of childhood morbidity and mortality in most developing countries, with Enteropathogenic Escherichia coli (EPEC) being one of the most important aetiologic agents of children under-five years diarrhea in many of these countries. In Indonesia especially Pekanbaru, the epidemiology of these EPEC have not been well studied. During the period from April 2014 to September 2014, 47 stool sample were collected from children under-five years with acute diarrhea in the hospitality primary health care in Pekanbaru and the examination has been done in Microbiology Laboratory of Medical Faculty Riau University. The Escherichia coli were isolated and diagnosed by standard microbiological methods. The isolates confirmed to be Esherichia coli were subjected to a slide agglutination test with Escherichia coli polyvalent antisera. This study was a descriptive study using a consecutive sampling method to describe the characterization of Enteropathogenic Escherichia coli (EPEC) infection on children under-five years at the hospitality primary health care in Pekanbaru. Based on gender and age from all specimens that were collected, the diarrhea mostly found in male (59.5%), and in 12-59 months patients (93.6%). Out of the 47 stool samples, 1 isolate (2.2%) were positive for EPEC. The isolate was recovered from the 19 months female.Key words: diarrhea, enteropathogenic Escherichia coli, EPEC, children under-five years, hospitality primary health care